Razvoj prebavil - Zorc-Pleskovič, Ruda (Medicinski razgledi, 2004)
Digestive system arises from the primitive endodermally lined gut tube, which is bounded cranially by the oropharyngeal membrane and caudally by the cloacalmembrane. The gut is divided into foregut, midgut, and hindgut segments. The primordium of the liver arises in the septum transversum, but asit expands, it protrudes into the ventral mesentery. The pancreas grows out as dorsal and ventral pancreatic buds that ultimately fuse to form a single pancreas.
Keywords: Digestive System; Prebavila; Embryology; Jetra; Esophagus; Požiralnik; Stomach; Trebušna slinavka; Želodec; Intestine, Small; Intestine, Large; Črevo debelo; Črevo tanko; Liver; Pancreas; embriologija